Motivation and arabic learning achivement : a comparative study between two types of Gansu Islamic Schools in China - Qiao, Khadijah Juping (Institute of Education, International Isalmic University Malaysia, 2012)
Motivation is one of the most highly studied issues within the field of L2 learning. A number of theories of motivation have been used to explain the effects of motivation on L2 learning. The Self-determination theory (SDT), a popular motivational theory developed by Ryan and Deci (1985), has been applied by many L2 researchers to explicate the relationship between motivation and L2 learning outcomes from social and psychological perspectives. In addition, SDT distinguishes intrinsic motivation from extrinsic motivation on L2 learning achievement. Bakar et al. (2010) in their study extended Ryan and Deci's self-determination theory to investigate the role of religious motivation in Arabic (L2) language learning achievement. This study sought to extend previous findings by examining the relationship between motivation aspects: Religious Motivation (RM), Internal Motivation (IM), External Motivation (EM), and Amotivation (AM) and Arabic language learning achievement. Specifically, it aims to a) explore factors that influence Arabic learning achievement and examine the relative contribution of the different aspects of motivation (RM, IM, EM and AM) on Arabic language learning achievement; b) investigate the relationship between those aspects; and c) compare the level of motivation across two subgroups of Arabic language learners. To achieve these purposes, 348 students were randomly selected from two types of Gansu Islamic schools in China to complete a 36-item questionnaire. Interviews were also conducted with four respondents to get more in-depth information as regards Arabic language learning. Qualitative analysis was conducted to answer the first research question, while the Rasch Measurement Model, independent sample t-test, Person correlations, and multiple regression analysis were utilized to answer the other research questions. The qualitative analyses indicated that there are some positive and negative factors (internal and external) that affect student learning of Arabic language either positively or negatively. Among the positive factors are religion, positive attitudes towards learning Arabic, and finding a more prestigious job. On the other hand, the negative factors include, lack of motivation to learn Arabic and the teaching methodology. The quantitative data showed significant correlations among all the motivation aspects except Amotivation. The multiple regression analyses indicated that AM and RM were significant predictors of Arabic language learning. To conclude, all the motivation aspects influence students' Arabic learning achievement either positively or negatively. Religion and a positive attitude towards Arabic language learning motivate students to do better in learning the language, while Amotivation and inappropriate teaching methodology deter students from learning Arabic effectively. Direct intervention and new learning and teaching strategies should be formulated to promote effective learning of Arabic language.